Altered editing level of microRNAs is a potential biomarker in lung adenocarcinoma. Issue 10 (6th September 2018) - Maemura, Keita; Watanabe, Kousuke; Ando, Takahiro; Hiyama, Noriko; Sakatani, Toshio; Amano, Yosuke; Kage, Hidenori; Nakajima, Jun; Yatomi, Yutaka; Nagase, Takahide; Takai, Daiya
Abstract : Adenosine‐to‐inosine (A‐to‐I) microRNA editing is associated with tumor phenotypes in various cancer types. Recent analyses of The Cancer Genome Atlas (TCGA) dataset have shown several microRNAs that undergo A‐to‐I editing in human cancers, some of which have been reported to be associated with prognosis. Herein, we examined published small RNA deep sequencing data of 74 cases of lung adenocarcinoma (AD) and the corresponding normal counterpart (NC) specimen in silico in order to identify A‐to‐I microRNA editing events. Editing levels of miR‐379‐5p, miR‐99a‐5p, and miR‐497‐5p were lower in AD than in NC and, in a large number of cases, the editing level of miR‐200b‐3p was higher in AD than in NC. Difference in the editing level between AD and NC was largest for miR‐99a‐5p. Then, we examined the editing level of miR‐99a‐5p in 50 surgically resected lung adenocarcinoma cases at our institution by a conventional sequence‐based method, and its association with clinical outcomes. The editing level of miR‐99a‐5p was significantly lower in 19 cases of AD (38%) than in corresponding NC. These cases showed a shorter overall survival as assessed using the log‐rank test ( P  = .047). This trend was consistent with previous analyses of TCGA dataset. The altered editing level of microRNAs in lung adenocarcinoma could serve as a potential biomarker. Abstract : We compared the editing levels of miR‐99a‐5p between cancerous tissues and corresponding normal tissues from 50 cases of lung adenocarcinoma at our institution. Nineteen cases with significant loss of editing in adenocarcinoma showed a shorter overall survival ( P  = .047). The altered editing level of microRNAs in lung adenocarcinoma could serve as a potential biomarker.